Analisis Perbedaan Kinerja Keuangan Pada Koperasi Mandiri Di Kabupaten Banyuwangi Atas Jasa Kantor Akuntan Publik - Yuhertiana, Indrawati; Arsilo Sofyan, Donny (Jurnal Riset Ekonomi dan Bisnis, 2007)
There are three sectors that give  contribution in Indonesia economics, those are private sectors, co-operation and public sectors. Co-operation, that frequently called as “soko guru” Indonesia economics do not have a significant development. There  are many evidence that make co-operation have a bad performance, many trouble in mismanagement, that make this institusion are not developed.Such kind of trouble is the lack of human resourcess skill in accounting. Accounting is needed in business to inform the right performance of the entity, It is also needed for the stakeholder to make a right decision on business. The role of public accountant to consultate co-operation in improving their skill in accounting is needed. Hopefully by the assistance of a public accountant, co-operation can improve their financial performance, so the entity could eficiently operationalized.The purpose of this research is to examine the role of public accountant in its assistance in co-operation work. Therefore, it was examined the difference of co-operation financial performance in co-operation that have  accountant public assistance and co-operation that have not accountant public assistance.Sample of this research are co-operation that located in Banyuwangi. Financial performance ratios, those are  net profit margin ration, current ratio and debt ratio used as variables in this research. The statistics tools to examine the hypotheses is t test.The research found that there are no differences in co-operation that use accountant public and none.Keywords: Net Profit Margin, Current Ratio, Debt Ratio, Financial Performance, Co-Operation, Public Accountant